ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA (STUDI KASUS MAHASISWA AKADEMI ENTREPRENEURSHIP TERANG BANGSA SEMARANG) - Erlitawati Kaharudin; Alexander Nova Vernando (Program Magister Manajemen Indo Global Mandiri University, 2020)
This study discusses the faktors that influence the entrepreneurial interest of the students in Semarang Terang Bangsa Academy. This study uses quantitative analysis methods with multiple linear regression methods to propose hypotheses between independent and dependent variables. The variables used are personality and family environment. The study population was active students of the Semarang Terang Bangsa Entrepreneurship Academy who had attended an entrepreneurship subject or had run a business. The sampling technique is done by using saturation sampling with a total sample of 64 students. The results of the study that showed the personality and environment of the family had a significant positive effect on the entrepreneurial interest of the students in Semarang Terang Bangsa Entrepreneurship Academy. Based on simultant research that shows positive personality and family environment variables on entrepreneurial interest in students of the Semarang Terang Bangsa Entrepreneurship Academy with a level of influence of 57.3% and a significance of 0,000.